Peripheral T-Cell Lymphoma of the Submandibular Salivary Gland as an Unusual Manifestation of Richter’s Syndrome: A Case Report and Literature Review - Gorodetskiy, Vadim R.; Probatova, Natalya A.; Kondratieva, Tatiana T. (Case Reports in Hematology, 2017)
Richter’s syndrome is the development of high-grade non-Hodgkin lymphoma (NHL) or Hodgkin lymphoma in patients with chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL). In most patients with Richter’s syndrome, the high-grade NHL is diffuse large B-cell lymphoma. Only a small minority of CLL/SLL patients develop T-cell malignancies. Herein, we describe a 40-year-old male patient presenting with peripheral T-cell lymphoma not otherwise specified (PTCL-NOS) in the submandibular salivary gland, two years after the diagnosis of CLL/SLL. The PTCL-NOS consisted of small lymphocytes, which complicated diagnosis. Immunohistochemical, cytological, and molecular studies allowed the correct diagnosis of composite lymphoma (SLL/PTCL-NOS) of the submandibular salivary gland. The PTCL-NOS had a cytotoxic phenotype and aberrant expression of CD79a. There was no evidence to suggest that the PTCL-NOS of the submandibular salivary gland developed from an intimately associated submandibular lymph node or by PTCL-NOS dissemination. A review of the literature and presented case suppose that the PTCLs developed following CLL/SLL have the cytotoxic phenotype and can clinically mimic typical Richter’s syndrome.